The role of culture and gender in women entrepreneurs based on McClelland’s theory - Nor Hanim, Awang @ Mohd Noor; Norfatiha, Othman; Mohd Shahidan, Shaari; Faiz, Masnan; Leha, Saliman; Roslina, Ismail; Norhayati, Sa'at (Springer Nature, 2025)
This study examines how cultural heritage and gender roles shape achievement motivation among 12 women entrepreneurs in the batik and songket industries in Kuala Terengganu, Terengganu and Kota Bharu, Kelantan, East Coast Malaysia, using McClelland’s theory of needs as a conceptual framework. The study operationalizes the constructs of need for achievement (nAch), power (nPow), and affiliation (nAff) to analyze how family attitudes, socialization, inherited skills, and personal interests influence entrepreneurial motivation in heritage business contexts. A qualitative case study design was employed, with participants selected through purposive and snowball sampling from a population of 458 registered entrepreneurs. Data were collected via semi-structured interviews and analyzed thematically to identify patterns linking cultural and gender factors to motivational drives. Findings show that intrinsic achievement motivation (nAch) predominates over profit motives, while nAff and nPow are expressed through collaborative networks and leadership in business operations. The study’s original contribution lies in linking family heritage and gender roles with McClelland’s motivational constructs, providing a framework to support women-led heritage entrepreneurship and preserve Malaysia’s cultural crafts.